Coupling between a bubble and a liquid-liquid interface in viscous flow. (March 2023) - Su, Hao-Chen; Liu, Yun-Long; Tian, Zhao-Li; Zhang, Shuai; Zhang, A-Man
Highlights: The improved Eulerian finite-element method considers viscosity. Studying the coupling between a bubble and liquid-liquid interface systematically. The pressure peaks caused by bubbles are nonlinearly related to viscosity and buoyancy. Abstract: The bubble dynamics are of great significance in the scientific community and have wide applications. Due to the complex coupling effect, high nonlinearities arise when the bubble is initiated at a liquid-liquid interface. Based on the Eulerian finite element method, the coupling model of a bubble and the liquid-liquid interface is established considering the viscosity and is verified by comparing with the experiments. It is found that the bubble only generates a downward jet at a large Reynolds number. In contrast, a pinch-off effect occurs due to an annular jet impact, which generates two opposite jets at a small Reynolds number. And the bubble migrates upward with the increase of buoyancy parameters. Moreover, through dynamic analysis, we find three reasons for the pressure peaks above the bubble: the annular jet impact, the downward jet impact, and the upward jet passing the measuring point. It is found that the pressure peaks are nonlinearly related to viscosity and buoyancy, and they can enhance each other to generate higher pressure peaks.